Description Of Factors Influencing Stroke In Early Adults At Rsu Imelda Medan - Gultom, Satriani; Candra Damanik; Syahrul Handoko; Yuni Shanti; Ali Asman Harahap; Arta Marisi Dame (SEAN Institute, 2023)
Stroke is a disease that most often causes disability in the form of paralysis of the limbs, speech disorders, thought processes, memory, and other forms of disability as impaired brain function. In general, people think that stroke is a disease that only occurs in middle age and old age. In fact, 10% of strokes occur at a relatively young age (less than 45 years). But now there is also a trend in patients under 45 years of age. According to WHO in 2012, 51% of deaths from stroke worldwide are caused by high blood pressure. Based on the results of the 2013 Riskesdas, the prevalence of stroke in Indonesia increases with age. The highest cases of stroke diagnosed by health workers were 75 years and over (43.1%) and the lowest were in the age group 15-24 years (0.2%). The prevalence of stroke based on gender is higher for males (7.1%) than for females (6.8%). Based on place of residence, the prevalence of stroke in urban areas is higher (8.2%) compared to rural areas (5.7%). This research was conducted in May 2017 which was descriptive in nature with the aim of getting an overview of the factors that influence the occurrence of stroke in early adulthood at the Imelda general hospital, Indonesian workers in Medan. This research technique used a sample method of 30 respondents. The results of this study showed that the most influential risk factors for the incidence of stroke in early adulthood were lifestyle, namely eating and drinking habits (89.1%), hypertension (84.3%), family history (84.3%) , obesity (83%), smoking (67.6%), and physical activity (30%). Eating and drinking habits have a high influence, because in their daily lives they consume the foods they like and what they want to eat without thinking that these foods are at risk of causing degenerative diseases. factors that influence the occurrence of stroke in early adulthood, so that the family's knowledge of stroke patients increases.